Characterization of the complete mitochondrial genome of the Dayu yak (Bos grunniens). Issue 1 (2nd January 2021) - Guo, Shaoke; Ma, Haiqing; Zhao, Qingzhang; Za, Xita; Li, Jian; Kang, Haiyan; Pei, Jie; Guo, Xian
Abstract: Dayu yak ( Bos grunniens ) is a long-furred yak breed from the Qinghai-Tibetan Plateau, and is highly adapted to local high-altitude and cold environments. In this study, its mitochondrial genome was characterized via high-throughput sequencing technology. The genome is 16, 323 bp long with an AT-biased base composition (61.0% A + T; light strand), and harbors the typical set of 37 mitochondrial genes and a noncoding control region. Its gene arrangement is identical to those of other bovid taxa. Phylogenetic analysis suggests that Dayu yak is most closely related to Maiwa, Niangya, Qinghai Plateau, Xueduo and Yushu yaks.